The Performance of the Basso Continuo in Italian Baroque Music - Borgir, Tharald (Rochester Boydell & Brewer, 1991)
Covers the Italian Baroque period (1600-1730). Borgir rejects the notion that the basso continuo line is doubled by bass instruments and shows how these have an independent musical function in ensemble music. He untangles their confusing terminology and also explores the unexpected uses of the large lutes. Italian continuo practice included elaborate training in improvisation described in detail here for the first time.Tharald Borgir is professor emeritus in the music department at Oregon State University. His principal performance activities have been on the harpsichord and the fortepiano.
Keywords: 17th Century (1601-1700); 18th Century (1701-1800); Basso continuo; Historically informed performance; Italy